Modified of The Heated Electric Foot Bath Basin For Blood Pressure and Quality of Live in Hypertension Patient - Supardi, Supardi; Arwani, Arwani; Pujiastuti, Rr Sri Endang (Media Keperawatan Indonesia, 2024)
Hypertension has contributed as a trigger factor for death in all ages in Indonesia by 6.7%. One of the therapies in hypertensive patients is a warm water bath. Earth Leakage Circuit Breaker helps detect leakage currents, so foot soak therapy is effective for lowering blood pressure. The purpose is to develop the heated electric foot bath basin as an effort to lower blood pressure and improve quality of life in hypertensive patients. This research method is Research and Development with quantitative research design, using quasi-experimental design with pretest-posttest randomized control group design. The research was conducted at Pageruyung Health Center, Kendal Regency, with stratification random sampling. The results showed the effect of the heated electric foot bath basin in reducing systolic blood pressure from 157.67 to 147.17 and diastolic from 93.90 to 88.90. There was an effect of the heated electric foot bath basin on the quality of life of hypertensive patients, where the intervention group had a better quality of life (score 53.03) than the control group (score 43.73). Conclusion Heated Electric Foot Bath Basin developed by adding an ELCB (Earth Leakage Circuit Breaker) device was  able to improve the quality of life of hypertensive patients.